2013
DOI: 10.1016/j.ydbio.2013.02.022
|View full text |Cite
|
Sign up to set email alerts
|

Pattern and polarity in the development and evolution of the gnathostome jaw: Both conservation and heterotopy in the branchial arches of the shark, Scyliorhinus canicula

Abstract: The acquisition of jaws constitutes a landmark event in vertebrate evolution, one that in large part potentiated their success and diversification. Jaw development and patterning involves an intricate spatiotemporal series of reciprocal inductive and responsive interactions between the cephalic epithelia and the cranial neural crest (CNC) and cephalic mesodermal mesenchyme. The coordinated regulation of these interactions is critical for both the ontogenetic registration of the jaws and the evolutionary elabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 58 publications
(71 citation statements)
references
References 140 publications
4
67
0
Order By: Relevance
“…ScNodal, ScVg1, ScOtx5 and ScFgf8 antisense RNA probes were synthesized from cDNA fragments subcloned in pSPORT1 (ScNodal, ScVg1 and ScFgf8) or pTZ19R (ScOtx5), and sequenced using Universal M13 primers as previously described 31,43,45 . GenBank accession codes for the corresponding sequences are KP698591 for ScNodal, KP698592 for ScVg1, AAK85128.1 for ScOtx5, KP698593 for ScFgf8.…”
Section: Methodsmentioning
confidence: 99%
“…ScNodal, ScVg1, ScOtx5 and ScFgf8 antisense RNA probes were synthesized from cDNA fragments subcloned in pSPORT1 (ScNodal, ScVg1 and ScFgf8) or pTZ19R (ScOtx5), and sequenced using Universal M13 primers as previously described 31,43,45 . GenBank accession codes for the corresponding sequences are KP698591 for ScNodal, KP698592 for ScVg1, AAK85128.1 for ScOtx5, KP698593 for ScFgf8.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, there are no detailed studies about telencephalic tangential routes in basal vertebrates which prevent us from having a comprehensive view of forebrain evolution. The lesser spotted dogfish Scyliorhinus canicula represents a key species in evo-devo studies (Coolen et al 2009;Compagnucci et al 2013). It belongs to the class of Chondrichthyes (chondrichthyans or cartilaginous fishes), an ancient radiation of vertebrates considered the sister group of Teleostomi, i.e., the group of vertebrates with bony skeleton that gave rise to land vertebrates.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the lower jaw to upper jaw homeosis observed in Dlx5/6 mutant mice demonstrates the existence of a Hinge-centric patterning program [68]. Recent studies in a chondrichthyan have shown that genes with known polarized jaw expression patterns also have conserved Hinge-(Emx1/2, Nkx3.2) or Cap-centric (Dlx3, Prx1, Msx1, Tbx2, Bmp4) expression patterns (Figure 7.5A) [176]. However, at least some ventralizing signals in the mandible, such as Edn1, seem to be specific to the lower jaw [59,60].…”
Section: Cranial Nc Development and Evolutionmentioning
confidence: 87%